Effectiveness of multimethod, community-based educational interventions on the knowledge and attitude to birth preparedness and complications readiness among women in southwest Nigeria - Bosede B Afolabi; Ifeoma P Okafor; Mobolanle R Balogun; Adekemi O Sekoni; Duro C Dolapo; Claudia A Hawkins (BMJ Public Health)
Background Birth preparedness and complications readiness (BP/CR) is an effective strategy to reduce maternal and newborn morbidity and mortality.Aim To assess the effect of educational interventions on women’s knowledge and attitude regarding BP/CR in southwest Nigeria.Methods A quasi-experimental study was carried out over 1 year (May 2019–April 2020) in Lagos, southwest Nigeria. Intervention was delivered using multiple educational methods: health education sessions, information, education, and communication materials, and mHealth. A total of 2600 women were recruited by multistage sampling. Data were collected using interviewer-administered questionnaires and analysed with Epi Info and SPSS V.25 software. Summary and inferential statistics were done involving four-way analysis. The level of significance was set at p<0.05. Regression analysis applied to intervention group (IG). A 50% cut-off was used to categorise respondents into adequate and inadequate knowledge of BP/CR.Results Mean age of the respondents: 31.2±5.4 years for the IG, 30.4±6.0 years for the control group (CG); p=0.007. Most women in both groups had formal education, were employed and had their last antenatal care in health facilities. At baseline, both groups had overall inadequate knowledge of BP/CR which improved significantly post intervention only in the IG. For the IG: 9.4% (pre), 52% (post), (p<0.001); CG: 0.2% (pre), 0.5% (post), (Fisher’s exact p=0.624). Most respondents in both groups had a positive attitude to BP/CR, the intervention had no significant influence on this in the IG (p=0.504).Predictors of adequate knowledge of BP/CR included being of Yoruba tribe, (adjusted OR (AOR) 2.83, 95% CI 1.06 to 7.54), being employed, (AOR 1.31; 95% CI 1.04 to 5.87) and having a baby 6 months prior to the study (AOR 2.62; 95% CI 1.31 to 5.24).Conclusion Findings have implications for the design and implementation of relevant policy and community interventions to reduce maternal mortality. Further research can examine the role of financial exclusion in inadequate knowledge.